2021
DOI: 10.3390/polym13234175
|View full text |Cite
|
Sign up to set email alerts
|

Nano Drug Delivery Platforms for Dental Application: Infection Control and TMJ Management—A Review

Abstract: The oral cavity is an intricate environment subjected to various chemical, physical, and thermal injuries. The effectiveness of the local and systemically administered drugs is limited mainly due to their toxicities and poor oral bioavailability that leads to the limited effectiveness of the drugs in the target tissues. To address these issues, nanoparticle drug delivery systems based on metals, liposomes, polymeric particles, and core shells have been developed in recent years. Nano drug delivery systems have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…For instance, patients with certain health conditions that are experiencing unsuccessful treatments in oral regeneration. Therefore, acceleration of the healing process and the rise of antibacterial properties, associated with the development of personalized dental biomaterials, have been demonstrated to be the main focus of drug delivery biomaterials for oral tissue applications [ 4 , [131] , [132] , [133] ]. The translation of all current basic science into market products has a possibility for substantial improvements in oral treatments and general medicine.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, patients with certain health conditions that are experiencing unsuccessful treatments in oral regeneration. Therefore, acceleration of the healing process and the rise of antibacterial properties, associated with the development of personalized dental biomaterials, have been demonstrated to be the main focus of drug delivery biomaterials for oral tissue applications [ 4 , [131] , [132] , [133] ]. The translation of all current basic science into market products has a possibility for substantial improvements in oral treatments and general medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Lal et al [ 14 ] have found that combined NPs-based agents provide a more favourable release of drugs in a controlled manner and efficient delivery to the site of action. We hope that research will also contribute to the development of biopolymer nanofilled films used in dentistry, given their physicochemical properties, bioactivity and versatility.…”
Section: Discussionmentioning
confidence: 99%
“…Polymer nanomaterials, films, and coatings are widely used in various industries, including pharmaceuticals and medicine. Polymer tapes and films are used in equipment construction as working elements [ 1 , 2 ], to ensure the tightness of threaded joints during the life cycle of the product [ 3 , 4 ], for elastic fixation of broken bones during surgery on human limbs [ 5 , 6 ], for filtering liquids and gases [ 7 , 8 ], for aqueous nanostructures containing antimicrobials of natural origin have been developed to inactivate SARS-CoV-2 surrogates on surfaces [ 9 ], for wound healing [ 10 , 11 , 12 ] and dentistry [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In nanomedicine, microbubbles (MBs) have shown much promise in recent years because of their high encapsulation efficiency, targeted drug release, improved biocompatibility, and longer blood circulation time ( Zhou et al, 2010 , Lal et al, 2021 ). However, devices have to be designed to fabricate MBs at chair side.…”
Section: Introductionmentioning
confidence: 99%